Design and implementation of a web-based thesis guidance system using the waterfall method - Muslihah, Isnawati; Laksani, Hening; Bagaskara, Danendra (Journal of Soft Computing Exploration, 2025)
The advancement of technology and the internet has opened up opportunities for the development of information systems in higher education in Indonesia. One significant system is the online thesis guidance system for students. Currently, the guidance process at ISI Surakarta is conducted manually and face-to-face, which has proven to be less effective due to scheduling conflicts between students and lecturers, leading to delays in thesis progress. The development of the online thesis guidance system aims to facilitate interaction between lecturers and students while digitally storing review histories and revisions, enhancing the efficiency of administrative data collection. Additionally, the system is designed to provide announcements and timelines from proposal submission to eligibility examinations, helping students monitor their performance to graduate on time. The Waterfall method is employed in this system's design to ensure a systematic development process, covering all stages from requirements analysis to maintenance. This method allows early detection of potential conditions and ensures that user needs are met before the system is implemented. The implementation of this system is expected to improve the efficiency and quality of academic services, support students in completing their studies on time, and provide benefits to the entire academic community of ISI Surakarta.